Defensive Fortifications in the pre–Desert Zone of the Tripolitania Region A Study of Selected Defensive Fortification Models wadi al Mardum - Suleiman Milad Muftah Bin Garda (Journal of Scientific and Human Dimensions, 2025)
This Study examines the defensive fortifications that highlight the strategic and military importance of the Tripolitania region during the Roman period These structures formed a defensive line against threats originating from beyond the desert and contributed to securing the imperial frontier and maintaining communication between decision-making centers in urban settlements and the interior regions.The diversity in the layout, architectural style, and functions of these fortifications reflects their adaptation to the nature of their locations and their locations and their roles in protecting communication routes.Wadi Al-Mardum was selected as a key case study, being one of the most significant sites that preserves clear examples of such defensive structures. The architectural remains demonstrate a high level of planning, with sites carefully positioned to overlook roads and passages, enabling them to perform their intended functions effectively. The fortifications' dual role in protection and control, as most of them were established on elevated mountainous terrain.
Keywords: Defensive Fortifications; Tripolitania; Wadi Al-Mardum